2016
DOI: 10.1177/1079063216641109
|View full text |Cite
|
Sign up to set email alerts
|

Fantasy-Driven Versus Contact-Driven Users of Child Sexual Exploitation Material: Offender Classification and Implications for Their Risk Assessment

Abstract: Since the advent of the internet, convictions for the possession, display, trading and distribution of child sexual exploitation material (CSEM) have risen steadily, but little is known about the appropriate assessment and treatment of this offender group, especially in regards to their risk of reoffending. It has been suggested that a conceptual distinction of fantasy-vs. contact-driven CSEM users might be of merit. Sixty-eight offenders recruited from sex offender treatment providers were assessed via an ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 40 publications
2
57
0
2
Order By: Relevance
“…The empirical evidence suggests that individuals who have committed CSEM offences more likely present with deviant sexual interests than individuals who were convicted for a contact sex offence; however, they are also likely to have lifestyle and psychological barriers to contact offending (i.e., low victim access, greater victim empathy, or less antisociality) inhibiting them from acting on deviant interests, and were also found to be less likely to have access to children (Babchishin, Hanson, & VanZuylen, 2015; Seto, 2013; Seto, Cantor, & Blanchard, 2006; Webb, Craissati, & Keen, 2007). The existing research further suggests that, while for some individuals, their CSEM offending is linked to a sexual interest in children that may translate into offline spaces (i.e., contact-driven offenders ), there appears to be a distinct group who view CSEM seemingly without intent to commit a contact offence ( fantasy-driven offenders ; Merdian et al, 2018). Given that CSEM offenders in general, but fantasy-driven offenders in particular, display personal and offence-related characteristics distinguishing their treatment needs from those of contact sex offenders (Babchishin et al, 2015), existing theoretical and aetiological models of contact sex offending have been found to make a limited contribution to explain the aetiology and maintenance of CSEM offending (e.g., Middleton, Elliot, Mandeville-Norden, & Beech, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical evidence suggests that individuals who have committed CSEM offences more likely present with deviant sexual interests than individuals who were convicted for a contact sex offence; however, they are also likely to have lifestyle and psychological barriers to contact offending (i.e., low victim access, greater victim empathy, or less antisociality) inhibiting them from acting on deviant interests, and were also found to be less likely to have access to children (Babchishin, Hanson, & VanZuylen, 2015; Seto, 2013; Seto, Cantor, & Blanchard, 2006; Webb, Craissati, & Keen, 2007). The existing research further suggests that, while for some individuals, their CSEM offending is linked to a sexual interest in children that may translate into offline spaces (i.e., contact-driven offenders ), there appears to be a distinct group who view CSEM seemingly without intent to commit a contact offence ( fantasy-driven offenders ; Merdian et al, 2018). Given that CSEM offenders in general, but fantasy-driven offenders in particular, display personal and offence-related characteristics distinguishing their treatment needs from those of contact sex offenders (Babchishin et al, 2015), existing theoretical and aetiological models of contact sex offending have been found to make a limited contribution to explain the aetiology and maintenance of CSEM offending (e.g., Middleton, Elliot, Mandeville-Norden, & Beech, 2006).…”
mentioning
confidence: 99%
“…Consequently, different assessment and management strategies specifically developed for this offender group need to be explored (Merdian et al, 2018; Seto, Reeves, & Jung, 2010). Seto and Eke (2015) developed the first actuarial risk-assessment tool specific to CSEM offenders, the Child Pornography Offender Risk Tool (CPORT).…”
mentioning
confidence: 99%
“…22,28,29 It is estimated that likely 62% of child porn only cases would turnout to be contact offenses if polygraph is used. 21 Research has demonstrated that 40-85% of child porn only offenders self-reported having undetected contact victims 22,24,32 and polygraph would help in identifying those cases.…”
Section: Should the Use Of Polygraph Be Used As A Measure?mentioning
confidence: 99%
“…151 Approximately 50-85% of online offenders (soliciting children or child porn) admit to having committed a undetected contact offenses against a child. 123,173 Merdian et al, 174 found that nearly 40% of their sample self-reported contact victims though only nearly 3% were identified via criminal conviction data. More diversity in offending histories.…”
Section: Criminal Historymentioning
confidence: 99%